2021
DOI: 10.1021/acs.inorgchem.1c02468
|View full text |Cite
|
Sign up to set email alerts
|

Multi-interactive Coordination Network Featuring a Ligand with Topologically Isolated p Orbitals

Abstract: A tridentate 3-pyridyl-based ligand containing a hexaazaphenalene skeleton (3-TPHAP − ) with topologically isolated p orbitals was prepared by a onepot reaction. It was successfully reacted with a Co 2+ salt and a 1,4benzenedicarboxylic acid co-ligand to give a porous coordination network. In the structure, the hexaazaphenalene skeleton interacts with water to form an internal hydrogen bonding network, allowing the entire pore space to be revealed by single-crystal X-ray diffraction (SXRD). The network structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[42][43][44] Due to the intramolecular charge transfer nature of this transition, the excitation energy and extinction coefficient could be modulated by modifying the substituent groups. [40,41,45] The possibility of formation of singlet oxygen ( 1 O 2 ) via the energy transfer pathway was considered. The existence of 1 O 2 was confirmed by photooxidation of 1,5-dihydroxynaphthalene (1,5-DHN), which is typically used as a selective trap (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44] Due to the intramolecular charge transfer nature of this transition, the excitation energy and extinction coefficient could be modulated by modifying the substituent groups. [40,41,45] The possibility of formation of singlet oxygen ( 1 O 2 ) via the energy transfer pathway was considered. The existence of 1 O 2 was confirmed by photooxidation of 1,5-dihydroxynaphthalene (1,5-DHN), which is typically used as a selective trap (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…This quenching behavior indicated that TPHAP was acting as a photosensitizer and its excited state was able to transfer energy to oxygen molecules to generate reactive oxygen species (ROSs) [42–44] . Due to the intramolecular charge transfer nature of this transition, the excitation energy and extinction coefficient could be modulated by modifying the substituent groups [40,41,45] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating molecules into single crystalline porous materials could reveal a plethora of important information about guest structures 2 , 5 , 6 and host-guest interactions 7 10 , in addition to monitoring reaction intermediates 11 , 12 and detecting metastable species 13 , 14 . In particular, structure determination of complex organic molecules has garnered strong attention since this technique can be applied to non-crystalline solids 15 , oils 16 19 , and compounds that can only be obtained in trace amounts 20 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported SXRD analysis of polycyclic aromatic hydrocarbons encapsulated into Co-3TPHAP MOF 7 . Interestingly, the host-guest crystal structures contained several solvent molecules in the pore, which were highly ordered and could be fully resolved by crystallography.…”
Section: Introductionmentioning
confidence: 99%